2008
DOI: 10.1037/a0013771
|View full text |Cite
|
Sign up to set email alerts
|

Modeling longitudinal change in the language abilities of children with autism: Parent behaviors and child characteristics as predictors of change.

Abstract: The objective of the current study was to evaluate the patterns of longitudinal change in the language abilities of 28 children with autism during early and middle childhood. Results from fitting a series of multilevel models showed that children's rate of language growth was independently predicted by (a) children's responsiveness to others' bids for joint attention and (b) parents' responsiveness to their children's attention and activity during play. Both predictive relations could not be explained by initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
255
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(279 citation statements)
references
References 54 publications
16
255
1
4
Order By: Relevance
“…However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006). Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 92%
“…However, in this study, a significant correlation was found between the IJA and RJA skills of children with ASD, which is in line with the results of some other studies in young children with ASD (e.g., Bono, Daley, and Sigman, 2004;Dawson et al, 2004;Siller andSigman, 2008, Toth, Munson, Meltzoff, Dawson, 2006). Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level).…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 92%
“…On the one hand, as has been demonstrated for typically developing children, children with autism who experience sensitive parenting in the absence of frightened/frightening/dissociative behaviors outlined by Hesse and Main (2006) may be more likely to form secure attachments, which in turn support the development of their social and language skills. Indeed, Siller and Sigman (2002, 2008) have already documented a predictive relationship between responsive behavior – specifically, the degree to which mothers are able to synchronize their vocal behavior with their child’s focus of attention – and growth in language in children with autism. On the other hand, the level of socio-emotional and cognitive functioning in children with autism may affect their caregiver’s ability to perceive and read their signals and thus constrain the parent’s ability to respond consistently to these signals.…”
Section: Discussionmentioning
confidence: 99%
“…Toddlers with ASD who achieved "good" language outcomes (an age-equivalent [AE] score above 30 months on the Vineland Adaptive Behavior Expressive Communication Scale) had better RJA skills than those with "poor" outcomes (Paul et al, 2008). Preschoolers with ASD with better RJA skills demonstrated faster language acquisition than those who were initially less responsive (Siller & Sigman, 2008). Sociocognitive skills, including RJA, at 2.5 to 3.5 years of age were the strongest predictors of social communication problems at 9 to 11 years of age (Chiat & Roy, 2013).…”
Section: Variables That Influence Language Development In Toddlers Wimentioning
confidence: 99%